(untitled) (Global Journal of Medical Research, 2023)
Objective Our intention was to analyze production on the anti-vaccine movement and its implications for vaccination of the Brazilian population in the indexed scientific literature Methods We used the systematic scoping review to search the following databases PubMed Scopus Web of Science Burry Lilacs BVS and Scielo JBI and PRISMA-SCR international protocols were adopted for the search and screening of scope-related articles The guiding question was built through the acronym PCC population concept and context The information was extracted categorized regarding the relationship with the theme of the anti -vaccine movement and the implications for vaccination coverage of the Brazilian and or general population